Specific alkaline phosphatase activity as an indicator of phosphorus status in the plankton community of a - Enis Hrustić; Stijepo Ljubimir; Svjetlana Bobanović-Ćolić; Ingrid Ivančić (Ocean and Coastal Research)
We evaluated the seasonal phosphorus (P) status of the plankton community in the Ombla Estuary (OE) by using its specific alkaline phosphatase activity (sAPA). Microphytoplankton (MICRO) indicated a substantially higher P deficiency than nanophytoplankton (NANO) and picoplankton (PICO). We found that the prolonged increase in the temperature of the surface estuarine water supported a notable growth of the dinoflagellate Prorocentrum spp. in late spring-early summer (June). In the summer (August), we found the maximum microphytoplankton sAPA (MICRO sAPA) (307.8  nmol μg C-1 h-1) in the surface water, in which (84%) dinoflagellates predominated within MICRO with the maximum alkaline phosphatase activity (APA) in all size fractions, including free enzymes. Persistently low discharge of Ombla during summer-early autumn caused a transition from phosphorus- to potentially nitrogen-limited MICRO in the surface water in early autumn (October). Nutrient stress disappeared in winter, in which a significant amount of dissolved orthosilicate, dissolved inorganic nitrogen (DIN), and soluble reactive phosphorus (SRP) enriched the estuary via maximal river discharge and inflow of nutrient-rich coastal waters. MICRO (coccolithophorids and diatoms) had very low APA (surface water) and quantitatively undetectable APA (bottom water) in the nutrient-rich water column in January. This study shows a more significant impact of nutrient concentrations on MICRO than other size classes of the plankton community. Because of the similarity in seasonal hydrological features, we assume that the general pattern of switching from P- to N-limitation of phytoplankton growth also occurs in other highly stratified estuaries along the coastal karst of the eastern Adriatic Sea during the lowest river discharges and groundwater activities in summer-early autumn before the rainy season. This study indicates that a common highly stratified estuary on the eastern Adriatic coast can serve as a natural laboratory to explore connections between nutrient limitations and phytoplankton successions.